Composite 3D printing stent with time sequence regulation blood vessel and bone tissue regeneration as well as preparation method and application of composite 3D printing stent
By loading osteogenic inducers and angiogenic differentiation inducers with different degradation rates into 3D printed scaffolds and printing them according to the reverse physiological repair sequence, composite scaffolds with different inner and outer layers were prepared, which solved the problem that existing scaffolds could not simulate vascularization and osteogenesis, and achieved effective regeneration of bone defects.
Patent Information
- Application Number
- CN202511486607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2026-01-20
AI Technical Summary
Existing bone tissue engineering scaffolds are unable to simulate the physiological repair process of vascularization followed by bone formation, neglecting the reconstruction of blood vessels in bone defect repair, resulting in poor bone regeneration effects.
Osteogenic inducers and angiogenic differentiation inducers were loaded onto two carrier materials with different degradation rates. Following the reverse order of the physiological repair process of vascularization followed by osteoogenesis, a composite 3D-printed scaffold with an inner layer loaded with osteogenic inducers and an outer layer loaded with angiogenic differentiation inducers was prepared by 3D printing, achieving time-sequential release and simulating the physiological self-repair process.
By sequentially releasing angiogenesis-inducing and osteogenic-inducing agents, bone regeneration of bone defects is promoted, achieving vascularization first and then osteoogenesis, thus improving the bone regeneration effect and exhibiting good biocompatibility and mechanical properties.
Smart Images

Figure CN121360294A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of biomedical materials and its manufacturing, more particularly, relates to a composite 3D printing scaffold with time sequence regulation of blood vessel and bone tissue regeneration and its preparation method and application. BACKGROUND
[0002] Extensive bone defects caused by severe trauma, infection, tumor-like lesion resection, osteoporosis, and congenital genetic diseases of abnormal bone development are very common in clinical practice. The repair of bone defects is still a difficulty for orthopedic surgeons. The current common medical repair methods for traditional treatment of bone defects include autologous bone transplantation, allogeneic bone transplantation, xenogeneic bone transplantation and metal implant. However, such traditional bone defect repair methods (such as autologous bone transplantation, allogeneic bone transplantation, metal implant) have inherent limitations such as limited donor source, immune rejection, mechanical mismatch, and inability to customize. Under the driving of the urgent needs in clinical practice, bone tissue engineering scaffolds emerge as the times require. Bone tissue engineering scaffold is a three-dimensional (3D) scaffold loaded with seed cells, cytokines or bioactive factors, which is conducive to cell adhesion, proliferation and differentiation after implantation, provides a suitable environment for the growth of primitive mesenchymal stem cells, and thus promotes bone tissue regeneration. It can be used as a kind of biomedical material or self-repairing material. At present, bone tissue engineering scaffolds mainly include polymer material scaffolds, bioceramic material scaffolds and composite material scaffolds.
[0003] Among them, the polymers used in bone tissue engineering scaffolds include natural polymers and artificially synthesized polymers, but natural polymers have insufficient mechanical strength and cannot accurately control the degradation rate; while artificially synthesized polymers also have some shortcomings, such as poor cell affinity, difficult to dissolve in water, and some polymers release acidic degradation products such as polylactic acid (PLA) after degradation, which induces inflammatory response and local tissue swelling in the body. Commonly used bioceramic materials such as hydroxyapatite (HA) are the main components of natural bone, which can be combined with tissues through chemical bonds and form new bone tissue after implantation, but due to the poor mechanical properties of HA, the new bone formed in the porous HA scaffold cannot bear the mechanical load required for remodeling.
[0004] Composite scaffolds are made of two or more different materials, although they can combine the advantages of different materials, the construction of bone tissue engineering scaffolds is very complex, and the shape, mechanical properties, composition materials, void size, shape, and void cross-linking characteristics of the scaffold are all factors that need to be considered when constructing the scaffold. Therefore, different composite scaffolds need to be studied for different purposes. For example, to improve the biocompatibility of the scaffold, patent CN111097068A uses hydroxyapatite particles, gelatin and sodium alginate to make a composite 3D printed scaffold with good biocompatibility, wherein the hydroxyapatite particles have osteogenic activity and bone induction, thereby promoting bone tissue regeneration and repair. To improve the bone regeneration ability of the composite scaffold, bone morphogenetic protein-2 (BMP-2) is loaded on the HA / collagen / polylactic acid scaffold, and the new bone deposition is faster than the pure scaffold, but the BMP-2 protein has secondary and tertiary structures, and is prone to protein denaturation during transportation or storage. Moreover, the ideal bone tissue engineering scaffold is to simulate the physiological repair process of bone defect, that is, to vascularize first and then to bone. However, the existing bone tissue engineering scaffold focuses on how to promote bone regeneration, ignoring the fact that the reconstruction of blood vessels also needs to be considered in the construction of bone tissue. However, how to realize the physiological self-repair process of vascularization first and then bone formation in the repair of bone defects is a technical difficulty that needs to be overcome in the existing field of bone tissue engineering. SUMMARY
[0005] In view of the above defects or improvement needs of the prior art, the present application provides a composite 3D printed scaffold with time sequence regulation of blood vessels and bone tissue regeneration and a preparation method and application thereof, which aims to find that by loading osteogenic inducer and vascular induction differentiation agent into two carrier materials with different degradation rates respectively, and 3D printing in the reverse order of the physiological self-repair process of vascularization first and then bone formation, a composite 3D printed scaffold capable of time sequence release of vascular induction differentiation agent and osteogenic inducer is made, which can simulate the physiological repair process of vascularization first and then bone formation as a biomedical self-repair material, and the bone regeneration effect is remarkable, thereby solving the technical problem that the existing 3D printed scaffold for bone defect repair is difficult to simulate the physiological repair process of vascularization first and then bone formation.
[0006] To achieve the above-mentioned purpose, according to one aspect of the present application, a preparation method of a composite 3D printed scaffold with time sequence regulation of blood vessels and bone tissue regeneration is provided, which comprises the following steps: loading osteogenic inducer and vascular induction differentiation agent into two carrier materials with different degradation rates respectively, and 3D printing in the reverse order of the physiological self-repair process of vascularization first and then bone formation; first mixing the slow-release carrier loaded with osteogenic inducer with nano-hydroxyapatite, and then 3D printing at a low temperature below 0°C to make a scaffold skeleton, which is loaded with slow-release osteogenic inducer at the same time of forming the 3D printed scaffold skeleton; The fast-release carrier loaded with the blood vessel inducing differentiation agent is coated on the 3D printing scaffold framework again, and a composite 3D printing scaffold with different layers is constructed, so that the inner layer is loaded with the osteogenic induction agent and the outer layer is loaded with the blood vessel inducing differentiation agent. The osteogenic induction agent comprises BMP-2 and OGP peptide; and the blood vessel inducing differentiation agent comprises VEGF and QK peptide.
[0007] Preferably, in the preparation method, the osteogenic induction agent is OGP peptide, and the amino acid sequence is shown in SEQ ID NO: 1, SEQ ID NO: 2, SEQ ID NO: 3 or SEQ ID NO: 4.
[0008] Preferably, in the preparation method, the blood vessel inducing differentiation agent is QK peptide, and the amino acid sequence is shown in SEQ ID NO: 5, SEQ ID NO: 6, SEQ ID NO: 7, SEQ ID NO: 8 or SEQ ID NO: 9.
[0009] Preferably, in the preparation method, the low temperature is 0℃-20℃.
[0010] Preferably, in the preparation method, the slow-release carrier, nano-hydroxyapatite and OGP peptide are mixed in a mass ratio of 200:100:1-160:40:1, and are co-melted in a 1,4 dioxane solution; a 3D printer is used for low-temperature printing, and the printing parameters are as follows: printing speed 20-55 mm / s, pneumatic pressure 80-150 kPa, receiving plate temperature-10℃ to-20℃, and printing needle 27G; after 3D printing, the scaffold framework is low-temperature freeze-dried; and the slow-release carrier is a hydrophobic polymer. The freeze-dried scaffold framework is immersed in a fast-release carrier solution containing QK peptide, and ultraviolet light is used for photocuring, so as to obtain a composite 3D printing scaffold with time-regulated blood vessel and bone tissue regeneration; and the fast-release carrier is a hydrogel material or a hydrophilic polymer.
[0011] Preferably, in the preparation method, the slow-release carrier is selected from PLGA and PCL; and the fast-release carrier is selected from gelatin, sodium alginate, collagen and methacrylated dextran.
[0012] Preferably, in the preparation method, the fast-release carrier is methacrylated dextran, and the mass ratio of the QK peptide to the methacrylated dextran is 1:50-1:100.
[0013] According to another aspect of the present application, a composite 3D printing scaffold with time-regulated blood vessel and bone tissue regeneration is also provided, which is prepared according to the preparation method of the present application.
[0014] According to another aspect of the present application, there is also provided a use of a composite 3D printed scaffold with time sequence regulation of blood vessels and bone tissue regeneration in preparation of a self-repairing medical material for bone defects.
[0015] Preferably, the use, the composite 3D printed scaffold is used in preparation of a self-repairing medical material for diabetic bone defects.
[0016] Overall, compared with the prior art, the above technical solutions conceived by the present application can achieve the following beneficial effects: The present method loads the osteogenic inducer and the vascular induction differentiation agent into two carrier materials with different degradation rates respectively, and performs 3D printing and gel coating modification in the reverse order of the physiological repair process of vascularization first and then osteogenesis, so as to prepare a composite 3D printed scaffold loaded with the osteogenic inducer in the inner layer and the vascular induction differentiation agent in the outer layer, which can release the vascular induction differentiation agent and the osteogenic inducer in time sequence. After the composite 3D printed scaffold is implanted into the body as a medical material, the composite 3D printed scaffold can realize the repair and regeneration process of vascularization first and then osteogenesis by the way of gel coating degradation first and then 3D printed scaffold degradation according to the different degradation rates of the composite materials, so as to well match the physiological regeneration needs of diabetic bone defects. The composite 3D printed scaffold provided by the present application has good life compatibility, biological activity and mechanical properties, and has a good application prospect in the treatment and self-repair of bone defects as a biomedical material. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 Fig. 1 is a photograph of different 3D printed scaffolds, and B to D are scanning electron micrographs of different 3D printed scaffolds, and E is the Ca, P element analysis result of different 3D printed scaffolds.
[0018] Figure 2 Fig. 2 is a Fourier infrared spectrum scanning of different composite 3D printed scaffolds, B is an X-ray photoelectron spectrum of different composite 3D printed scaffolds, and C is a mechanical property test of different composite 3D printed scaffolds.
[0019] Figure 3 Fig. 3 is a calcium element release of different 3D printed scaffolds, B is a phosphorus element release of different 3D printed scaffolds, C is a static hydrophilic angle of different 3D printed scaffolds, and D is the release rate of OGP and QK on the PHOQ scaffold.
[0020] Figure 4 Fig. 4 is the influence of different 3D printed scaffolds on the proliferation activity of MC-3T3-E1 cells.
[0021] Figure 5 Fig. 5 is Calcein / PI staining of different 3D printed scaffolds, and B is a live and dead proportion statistical column chart of different 3D printed scaffolds. Figure 6 are the results of the skeleton staining of MC-3T3-E1 cells on different composite 3D printing scaffolds.
[0022] Figure 7 A is the HUVECs migration test in vitro of different composite 3D printing scaffolds, and B is the statistical column chart of the HUVECs migration rate of different composite 3D printing scaffolds.
[0023] Figure 8 A is the HUVECs tube formation test, B is the statistical column chart of the number of nodes, C is the column chart of the total length of the tube formation, D is the mRNA expression amount of the VEGF gene, and E is the mRNA expression amount of the NOTCH-1 gene.
[0024] Figure 9 A is the alkaline phosphatase (ALP) staining, B is the alizarin red staining (ARS), C is the statistical column chart of the ALP positive area proportion, and D is the statistical column chart of the ARS positive proportion.
[0025] Figure 10 A is the Micro-CT scanning reconstruction, B is the bone mineral density (BMD), C is the BV / TV, and D is the regenerated bone volume.
[0026] Figure 11 A is the HE staining result, B is the Masson staining result, C is the NB / TB statistical column chart, and D is the LB / TB statistical column chart.
[0027] Figure 12 A is the alkaline phosphatase (ALP) staining, B is the statistical column chart of the alkaline phosphatase (ALP) staining, C is the osteocalcin (OCN) staining, and D is the statistical column chart of the osteocalcin (OCN) staining.
[0028] Figure 13 A is the CD206 immunofluorescence staining, B is the CD31 staining, C is the CD206 statistical column chart, D is the CD31 statistical column chart, and E is the statistical column chart of the blood vessel diameter. DETAILED DESCRIPTION
[0029] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and should not be used to limit the present application. In addition, the technical features involved in each embodiment of the present application described below can be combined with each other as long as they do not conflict with each other.
[0030] Different from other tissues, the normal bone tissue around the bone defect tissue can provide seed cells for the bone regeneration of the defect site. Although the defect repair can be completed by only filling with a scaffold material, how to recruit more seed cells and achieve the time-release of different bioactive factors to simulate the physiological repair process of the early vascularization and then the bone formation is the main consideration factor of the present application.
[0031] The present application finds that the osteogenic induction agent and the vascular induction differentiation agent are respectively loaded into two carrier materials with different degradation rates, 3D printing is performed in the reverse order of the physiological repair process of the early vascularization and then the bone formation, the slow-release carrier loaded with the osteogenic induction agent is mixed with nano-hydroxyapatite, and then 3D printing is performed under low-temperature conditions to manufacture the scaffold framework loaded with the slow-release osteogenic induction agent; the fast-release carrier loaded with the vascular induction differentiation agent is coated on the 3D-printed scaffold framework to construct the composite 3D-printed scaffold with the inner layer loaded with the osteogenic induction agent and the outer layer loaded with the vascular induction differentiation agent, and the composite 3D-printed scaffold can be used as a medical material to realize the rapid release of the vascular induction differentiation agent in vitro or in vivo to promote the early vascularization, the slow-release carrier is gradually degraded, the osteogenic induction agent is continuously and slowly released, and the osteogenic process in the middle and late stages is dominated. Especially, the osteogenic induction agent is osteogenic growth peptide (OGP peptide), and the vascular induction differentiation agent is a short peptide (QK peptide) simulating vascular endothelial growth factor, and it is found that the two have a synergistic effect and can synergistically promote the bone regeneration of the bone defect, and the effect is obviously better than that of single OGP peptide and QK peptide.
[0032] Based on this, the present application provides a preparation method of a composite 3D-printed scaffold with time-regulated vascular and bone tissue regeneration, which comprises the following steps: The osteogenic induction agent and the vascular induction differentiation agent are respectively loaded into two carrier materials with different degradation rates, 3D printing is performed in the reverse order of the physiological repair process of the early vascularization and then the bone formation, the slow-release carrier loaded with the osteogenic induction agent is mixed with nano-hydroxyapatite, and then 3D printing is performed under low-temperature conditions to manufacture the scaffold framework loaded with the slow-release osteogenic induction agent; the low temperature is 0℃~-20℃, and the printing under low-temperature conditions is beneficial to maintaining the biological activity of the osteogenic induction agent and avoiding the destruction of the activity by high temperature.
[0033] The fast-release carrier loaded with the vascular induction differentiation agent is coated on the 3D-printed scaffold framework to construct the composite 3D-printed scaffold with different layers, so that the inner layer is loaded with the osteogenic induction agent and the outer layer is loaded with the vascular induction differentiation agent.
[0034] The osteogenic induction agent includes bone morphogenetic protein-2 (BMP-2) and osteogenic growth peptide (OGP). The BMP-2 is a multi-effect growth factor belonging to the TGF-β superfamily, which is mainly involved in bone formation, tissue repair and development regulation. The OGP peptide is mainly involved in bone formation, bone marrow repair and osteoblast function regulation. The amino acid sequence of the OGP peptide is selected from ALKRQGRTLYGFGG (SEQ ID NO: 1), H-YGFGGGGGNVIGVIKKKRQRRRTKTSSCR-OH (SEQ ID NO: 2), H-VIKKR-OH or H-VIKKR-NH2 (SEQ ID NO: 3), or H-YGFGG-OH (SEQ ID NO: 4), wherein the H at the front of the sequence and the -OH / NH2 at the back are modification groups, which can be various, and are mainly amino acid sequences. The OGP is a strong bone formation promoting peptide, which can stimulate osteoblast proliferation, differentiation and mineralization, and promote bone matrix synthesis. Although the amino acid sequences of the OGP peptides are different in different studies, they all have the functions of promoting bone formation and bone repair. In some embodiments, the osteogenic induction agent is an OGP peptide, and the amino acid sequence thereof is ALKRQGRTLYGFGG as shown in SEQ ID NO: 1.
[0035] The vascular induction differentiation agent includes vascular endothelial growth factor (VEGF) and a short peptide (QK peptide) simulating vascular endothelial growth factor (VEGF). The QK peptide can simulate the activity of VEGF, specifically bind and activate the VEGF receptor, promote the proliferation, migration and lumen formation of vascular endothelial cells, and thus induce angiogenesis. The amino acid sequence of the QK peptide is selected from KLTWQELYQLKYKGI (SEQ ID NO: 5), H-LTWKLSPGP-OH (SEQ ID NO: 6), H-LTWKLAPGPKKK-NH2 (SEQ ID NO: 7), H-LTWKLSGPGKKK-NH2 (SEQ ID NO: 8), or H-LTWKLSPGPKKKC-OH / NH2 (SEQ ID NO: 9), wherein the H at the front of the sequence and the -OH / NH2 at the back are modification groups, which can be various, and are mainly amino acid sequences.
[0036] In some embodiments, the vascular induction differentiation agent is a QK peptide, and the amino acid sequence thereof is KLTWQELYQLKYKGI as shown in SEQ ID NO: 5.
[0037] Hydroxyapatite (HA) has a chemical composition similar to that of the mineral component of natural bone tissue, and has good biocompatibility and activity of promoting bone regeneration.
[0038] The slow-release carrier is selected from a slowly degradable hydrophobic polymer (such as PLGA, PCL). In some embodiments, the slow-release carrier is PLGA. After mixing the slow-release carrier loaded with osteogenic agents with nano-hydroxyapatite and then printing, the osteogenic agents can be loaded in the inner layer of the scaffold to achieve long-term slow release, avoid side effects caused by high doses, and enhance the mechanical properties of the scaffold. In addition, the degradation products of PLGA do not have a negative impact on fresh bone tissue, and can promote cell growth and angiogenesis through degradation products.
[0039] The fast-release carrier is selected from a rapidly degradable hydrogel material (such as gelatin, sodium alginate, collagen) or a hydrophilic polymer; in some embodiments, the fast-release carrier is methacrylated dextran (DexMA). After co-melting QK peptide with DexMA, the QK peptide is physically adsorbed, simply soaked, or coated on the surface or macroporous structure of the scaffold, and the DexMA hydrogel has excellent biocompatibility and biodegradability, which facilitates the rapid diffusion and release of QK peptide after the scaffold is implanted, and promotes early vascularization. In addition, the DexMA coating fills and connects the pores in the 3D printed scaffold, further improving the mechanical properties of the scaffold.
[0040] In some embodiments, the preparation method is as follows: PLGA (75:25), nano-hydroxyapatite (HA, particle size 50 nm), and OGP polypeptide (ALKRQGRTLYGFGG) are mixed in a mass ratio of 200:100:1 to 160:40:1 and co-melted in a 1,4-dioxane solution. A 3D printer is used for low-temperature printing, and the printing parameters are as follows: printing speed 20-55 mm / s, pneumatic pressure 80-150 kPa, receiving plate temperature -10 to -20°C, and printing needle 27G. After printing, the 3D printed scaffold is transferred to a low-temperature freeze dryer for freeze-drying treatment, cleaning, and freezing to obtain an OGP functionalized 3D printed PLGA / HA scaffold.
[0041] The above PLGA / HA scaffold is immersed in a composite DexMA hydrogel containing QK peptide (KLTWQELYQLKYKGI), and the composite 3D printed scaffold is photocured using 405 nm ultraviolet light for 3 minutes (25 mW / cm 2 ), to obtain a composite 3D printed scaffold with time-regulated blood vessel and bone tissue regeneration. The mass ratio of QK peptide to DexMA in the composite DexMA hydrogel containing QK peptide (KLTWQELYQLKYKGI) is 1:50 to 1:100.
[0042] The composite 3D printing scaffold prepared according to the method can time-release the vascular induction differentiation agent and the osteogenic induction agent on the scaffold in vivo after implantation, rapidly releases QK to promote early vascularization, and then continuously releases OGP to dominate subsequent osteogenesis, thereby realizing vascularization first and then osteogenesis, and avoiding the antagonism or competition effect caused by simultaneous release of the two factors. The time-release refers to the release of two or more active substances (such as OGP and QK) from the scaffold according to a pre-designed order and time point, which simulates the biological signals required in different stages of the natural tissue healing process.
[0043] The application further provides a composite 3D printing scaffold for time-regulated vascular and bone tissue regeneration, which is prepared according to the preparation method of the application.
[0044] The application further provides application of the composite 3D printing scaffold for time-regulated vascular and bone tissue regeneration in preparation of a bone defect self-repair medical material, wherein the composite 3D printing scaffold is prepared according to the preparation method of the application. In particular, the application is applied to preparation of a medical material for repairing diabetic bone defects.
[0045] The following is an example OGP generally refers to osteogenic growth peptide. It is a potent bone formation peptide that can stimulate osteoblast proliferation, differentiation and mineralization, and promote bone matrix synthesis.
[0046] QK generally refers to a short peptide simulating vascular endothelial growth factor. It can specifically bind and activate VEGF receptors, promote the proliferation, migration and lumen formation of vascular endothelial cells, and thus induce angiogenesis.
[0047] HA refers to hydroxyapatite, which has a chemical composition similar to the mineral composition of natural bone tissue, good biocompatibility and activity of promoting bone regeneration.
[0048] PLGA (polyglycolide-co-lactide) is a biodegradable synthetic polymer, also known as polylactic acid-glycolic acid copolymer, polylactic acid-glycolic acid copolymer or polyethylene glycol. PLGA is prepared by copolymerization of ethylene glycol and lactide as materials by ring-opening polymerization, direct melt polymerization and other processes, and has good biocompatibility and adjustable degradability. The degradation products do not cause negative effects on fresh bone tissue, and can promote cell growth and angiogenesis through degradation products.
[0049] DexMA (methacrylated dextran) is a water-soluble polymer prepared by grafting methacrylic acid ester onto dextran molecules. It has excellent biocompatibility and biodegradability, and DexMA hydrogel can be used as a 3D printing scaffold material to support cell growth and tissue regeneration.
[0050] The HA in the following examples was derived from Aladdin, H485315, the PLGA was derived from Shenzhen Maiqi Biological, Mqsw221101, the DexMA was derived from Suzhou Yongqinquan, EFL-DexMA-200k; the amino acid sequence of the OGP polypeptide was ALKRQGRTLYGFGG and the amino acid sequence of the QK polypeptide was KLTWQELYQLKYKGI, which were synthesized by Shanghai Qiangyao Biological Technology Co., Ltd. The experimental data was analyzed by SPSS software (version 22.0, IBM, USA), and the results were expressed as mean ± standard deviation. Single factor analysis of variance (ANOVA) and post hoc Tukey test were used to determine the statistical significance between groups, and p value < 0.05 was considered statistically significant.
[0051] Example 1 Preparation of different medical materials-composite 3D printed scaffold 1. Preparation of composite 3D printed scaffold with time-release OGP and QK The ideal bone regeneration process is usually vascularization first, then osteogenesis. To simulate the physiological healing process, this example prepared a composite 3D printed multilayer scaffold with time-release OGP and QK in the reverse order of the physiological healing process of bone injury, to achieve rapid release of QK (outer layer of bioactive ingredients) to promote early vascularization, and then sustained release of OGP (inner layer of bioactive ingredients) to dominate subsequent osteogenesis. The specific preparation is as follows: 1.1 Preparation of OGP functionalized 3D printed PLGA / HA scaffold (1) Preparation of 3D printing ink: 3.2 g of poly(lactide-co-glycolide) (PLGA) (75:25, molecular weight 100 k), 0.8 g of nano-hydroxyapatite (HA, particle size 50 nm) and 20 mg of OGP polypeptide (ALKRQGRTLYGFGG) were dissolved in 20 mL of 1,4-dioxane solution, and placed on a magnetic stirrer for stirring for 24 h to complete the preparation of the 3D printing ink.
[0052] (2) 3D printing of OGP functionalized PLGA / HA scaffold: the printing ink in (1) was printed using a 3D printer (Regenovo, Hangzhou Jetnofei) at low temperature, and the printing parameters were as follows: printing speed 50 mm / s, pneumatic pressure 0.1 MPa, receiving plate temperature -15°C, and printing needle 27G; after printing, the 3D printed scaffold was transferred to a low-temperature freeze dryer for freeze-drying treatment, then the scaffold was washed with double distilled water for 3 times, and freeze-dried again for standby.
[0053] 1.2 Preparation of composite 3D printed scaffold with time-release OGP and QK (1) Preparation of QK polypeptide-loaded methacrylated dextran (DexMA): 0.5 g of methacrylated dextran (molecular weight 500 k, EFL) and 5 mg of QK peptide (KLTWQELYQLKYKGI) were dissolved in a PBS solution containing 0.25% lithium phenyl (2,4,6-trimethylbenzoyl) phosphate salt (LAP) and were ready for use.
[0054] (2) Preparation of a composite 3D-printed scaffold for time-released OGP and QK: The composite DexMA gel prepared in (1) above was coated on the OGP-functionalized 3D-printed PLGA / HA scaffold prepared in 1.1, so that it completely immersed the 3D-printed scaffold, and then the composite 3D-printed scaffold was subjected to photocuring using 405 nm ultraviolet light for 3 minutes (25 mW / cm 2 ), to complete the preparation of the composite 3D-printed scaffold for time-released OGP and QK, which was again freeze-dried and stored at -20°C for standby use. The composite 3D-printed scaffold for time-released OGP and QK is abbreviated as PHOQ scaffold.
[0055] 2. Preparation of PH (1) Preparation of 3D-printing ink: 3.2 g of poly(lactide-co-glycolide) (PLGA) (75:25, molecular weight 100 k) and 0.8 g of nano-hydroxyapatite (HA, particle size 50 nm) were dissolved in 20 mL of 1,4-dioxane solution and placed on a magnetic stirrer for stirring for 24 h, to complete the preparation of the 3D-printing ink.
[0056] (2) 3D printing of OGP-functionalized PLGA / HA scaffold: The printing ink in (1) was subjected to low-temperature printing using a 3D printer (Regenovo, Hangzhou Jetonfei), with the printing parameters being: printing speed 50 mm / s, pneumatic pressure 0.1 MPa, receiving plate temperature -15°C, and printing needle 27G. After printing, the 3D-printed scaffold was transferred to a low-temperature freeze dryer for freeze-drying treatment, and then the scaffold was washed with double-distilled water three times, and was again freeze-dried and stored at -20°C for standby use, which is abbreviated as PH scaffold.
[0057] 3. Preparation of PHQ (1) Preparation of 3D-printing ink: 3.2 g of poly(lactide-co-glycolide) (PLGA) (75:25, molecular weight 100 k) and 0.8 g of nano-hydroxyapatite (HA, particle size 50 nm) were dissolved in 20 mL of 1,4-dioxane solution and placed on a magnetic stirrer for stirring for 24 h, to complete the preparation of the 3D-printing ink.
[0058] (2) 3D printing of OGP functionalized PLGA / HA scaffold: The printing ink in (1) was used for low-temperature printing using a 3D printer (Regenovo, Hangzhou Jetnofei), and the printing parameters were as follows: printing speed 50 mm / s, pneumatic pressure 0.1 MPa, receiving plate temperature -15°C, and printing needle 27G. After printing, the 3D printed scaffold was transferred to a low-temperature freeze dryer for freeze-drying treatment, then the scaffold was washed with double distilled water for 3 times, and freeze-dried again for standby.
[0059] (3) Preparation of QK polypeptide-loaded methacrylated dextran (DexMA): 0.5 g of methacrylated dextran (molecular weight 500k, EFL) and 5 mg of QK peptide (KLTWQELYQLKYKGI) were dissolved in a PBS solution containing 0.25% lithium phenyl (2,4,6-trimethylbenzoyl) phosphate salt (LAP) for standby. The prepared composite DexMA gel was coated on the 3D printed PLGA / HA scaffold prepared in (2) to completely immerse the 3D printed scaffold, and then the composite 3D printed scaffold was photocured using 405 nm ultraviolet light for 3 minutes (25 mW / cm 2 ), to complete the preparation of the composite 3D printed scaffold for time-release OGP and QK, and then stored at -20°C after freeze-drying again for standby, which is abbreviated as PHQ scaffold.
[0060] 4. Preparation of PHO (1) Preparation of 3D printing ink: 3.2 g of glycolide-lactide copolymer (PLGA) (75:25, molecular weight 100k), 0.8 g of nano-hydroxyapatite (HA, particle size 50 nm) and 20 mg of OGP polypeptide (ALKRQGRTLYGFGG) were dissolved in 20 mL of 1,4-dioxane solution and placed on a magnetic stirrer for stirring for 24 h to complete the preparation of the 3D printing ink.
[0061] (2) 3D printing of OGP functionalized PLGA / HA scaffold: The printing ink in (1) was used for low-temperature printing using a 3D printer (Regenovo, Hangzhou Jetnofei), and the printing parameters were as follows: printing speed 50 mm / s, pneumatic pressure 0.1 MPa, receiving plate temperature -15°C, and printing needle 27G. After printing, the 3D printed scaffold was transferred to a low-temperature freeze dryer for freeze-drying treatment, then the scaffold was washed with double distilled water for 3 times, and freeze-dried again for standby, which is abbreviated as PHO scaffold.
[0062] Example 2 Characterization of different composite 3D printed scaffolds The composite 3D printed scaffolds PHOQ, PH, PHQ and PHO were prepared according to the preparation methods of different 3D printed scaffolds in Example 1, respectively, and were characterized.
[0063] (1) Microtubule morphology The geometry and structure of different 3D-printed scaffolds were observed using scanning electron microscopy (SEM, ZEISS, Germany). The surface morphology of the samples was characterized using SEM at a working voltage of 3.0 kV. The elemental concentrations and distributions of Ca and P on the surface of the 3D-printed scaffolds were determined using energy dispersive spectroscopy (EDS). The results are as follows: Figure 1 As shown. Figure 1 In the figure, A represents the appearance of different 3D printed scaffolds, B to D represent the scanning electron microscope images of different 3D printed scaffolds, and E represents the Ca and P elemental analysis results of different 3D printed scaffolds.
[0064] Figure 1 As shown in Figure A, the four 3D-printed scaffolds, PHOQ, PH, PHQ, and PHO, all exhibit a clear fence-like structure with a distinct 3D-printed mesh pattern. Scanning electron microscopy (SEM) analysis reveals highly interconnected pores throughout the scaffold structure. Figure 1 (B to C). Notably, the pore morphology of the different 3D printed scaffolds differs: the PHO and PHOQ scaffolds exhibit irregularly shaped cavities, while the PH and PHQ groups primarily have circular pores. The pore size of the PHOQ group is smaller than that of the PH group; this difference may be attributed to the DexMA surface coating covering and filling some of the pores. Energy dispersive spectroscopy (EDS) analysis shows that C, O, Ca, and P are clearly detected on the surface of all different 3D printed scaffolds. Figure 1 (E). It is worth noting that the Ca and P contents of the PHQ and PHOQ groups were lower than those of the PH and PHO groups, which may be due to the DexMA coating on the surface of the 3D printed scaffold.
[0065] (2) Physicochemical characterization Different composite 3D printing scaffold materials were mixed and ground with KBr, and the 400~4000 cm⁻¹ diameter was analyzed using Fourier transform infrared spectroscopy (FTIR, Thermo, USA). -1 Variations in surface functional groups within the wavenumber range were investigated; the hydrophilicity of the scaffold was tested using a contact angle meter (Dataphysics, Germany); and the elemental composition and chemical state of the scaffold were analyzed using X-ray photoelectron spectroscopy (XPS, Thermo, USA). The mechanical properties of a composite 3D-printed scaffold with a diameter of 8 mm and a height of 8 mm were tested using a mechanical testing device (CARE, China). The compression rate was 1 mm / min, and the stress-strain curves of the composite 3D-printed scaffold were calculated using the measured loads and displacements. Results are as follows: Figure 2 As shown, Figure 2In the figure, A represents the Fourier transform infrared spectral scans of different composite 3D printed scaffolds, B represents the X-ray photoelectron spectra of different composite 3D printed scaffolds, and C represents the mechanical property tests of different composite 3D printed scaffolds.
[0066] like Figure 2 As shown in Figure A, Fourier transform infrared spectroscopy (FTIR) analysis results indicate that the four 3D printed scaffolds, PHOQ, PH, PHQ, and PHO, show significant differences in optical density at 1025, 1453, and 1749 cm⁻¹. -1 Characteristic absorption bands are present at all locations, corresponding to COC stretching, CH bending, and C=O stretching vibrations, respectively. Notably, the PHQ and PHOQ groups show absorption bands at 2917 cm⁻¹. -1 (CH vibration) and 3100-3650cm -1 An additional peak appeared at (OH vibration), confirming the successful DexMA coating on both PHQ and PHOQ 3D-printed scaffolds. XPS analysis detected characteristic peaks at 133.08 eV (P2p), 286.08 eV (C1s), 348.08 eV (Ca2p), and 530.08 eV (O1s), indicating that nano-hydroxyapatite was successfully integrated into the 3D-printed scaffold. Figure 2 (Middle B). Although Figure 2 The results in C indicate that modifying QK or OGP can reduce the mechanical properties of the scaffold to some extent, but the mechanical properties of the PHQ and PHOQ scaffolds are better than those of the PHO group. This may be because the DexMA coating fills and connects the pores in the 3D printed scaffold, thereby improving its mechanical properties.
[0067] (3) Detection of calcium, phosphorus, OGP and QK peptide release 3D-printed scaffolds (PHOQ, PH, PHQ, and PHO) with dimensions of 4 × 10 × 10 mm³ were prepared and placed in 10 mL of PBS solution. Supernatants were collected on days 1, 3, 5, 7, 10, and 15. Calcium and phosphorus content in the 3D-printed scaffolds was detected using inductively coupled plasma optical emission spectrometry (ICP-OES, PerkinElmer, USA), and release curves were plotted. Release curves of QK and OGP in the 3D-printed scaffolds were detected using BSA simulations. Supernatants were collected at the specified time points (days 1, 3, 5, 7, 10, 15, 20, 25, and 30), and release simulations were performed using a BCA protein assay kit. Results are as follows: Figure 3 As shown, Figure 3A represents the calcium element release of different 3D printed scaffolds, B represents the phosphorus element release of different 3D printed scaffolds, C represents the static hydrophilic angle of different 3D printed scaffolds, and D represents the release rate of OGP and QK on the PHOQ scaffold; in the figure, ‡ represents PHO vs. PH, p < 0.05; ❉ represents PHO vs. PHOQ, p < 0.05; ♟ represents PHOQ vs. PH, p < 0.05; § represents PHOQ vs. PHQ, p < 0.05; D is the comparison of OGP and QK release of the PHOQ scaffold, and * in the figure represents OGP vs. QK, p < 0.05.
[0068] Figure 3 The calcium and phosphorus release results show that there is no statistical difference in the Ca and P release rate between the PHQ scaffold group and the PH scaffold group, while the PHO scaffold group can release Ca and P elements more quickly than the other groups, indicating that OGP functionalization can promote the release of Ca and P of the 3D printed scaffold. Although compared with PHO scaffold, the DexMA coating after QK functionalization of PHOQ scaffold group shows slightly slower Ca and P release, but its Ca and P release speed is obviously better than that of PH and PHQ scaffold groups. Figure 3 A, B). Static water contact angle detection shows that after adding QK and OGP, the contact angle of the 3D printed scaffold gradually decreases, among which the hydrophilic angle in the PHOQ scaffold group is the smallest Figure 3 C), indicating that these 3D printed scaffolds after QK and OGP functionalization have stronger hydrophilicity, among which the PHOQ scaffold has the best hydrophilicity. Figure 3 D shows that the release rate of QK in the PHOQ scaffold is faster than that of OGP, which is very consistent with the healing process involved in bone healing (first blood vessels, then bone formation), and it is speculated that the PHOQ scaffold can be used as a biomimetic material to promote bone defect repair.
[0069] Example 3 Evaluation of the biocompatibility of different composite 3D printed scaffolds MC3T3-E1 cells are a mouse embryonic osteoblast precursor cell line with the ability to differentiate into osteoblasts and bone cells, and are used to study the application of different composite 3D printed scaffolds as medical materials in bone defect repair. In this embodiment, MC3T3-E1 cells are used to evaluate the biocompatibility of 3D printed scaffolds (PHOQ, PH, PHQ, PHO), as follows: (1) Cell proliferation MC3T3-E1 cells were seeded in 96-well plates on 3D printed scaffolds at a density of 5 x 10 3cells were seeded on the above-mentioned composite 3D printed scaffolds and incubated for 1 day. After PBS washing, the cells were stained with Calcein / PI solution, and then observed by confocal laser scanning microscope (CLSM, Nikon, Japan) for cell live / dead. The results of the effect of different 3D printed scaffolds on MC-3T3-E1 cell live / dead are shown in Figure 4 Figure 2A, and Figure 2B. In the figures, * indicates p<0.05, ** indicates p<0.01, **** indicates p<0.0001, and the same below.
[0070] Figure 4 The results show that the MC3T3-E1 cells cultured on the PHOQ, PH, PHQ, and PHO 3D printed scaffolds all showed a growth trend over time, with the MC3T3-E1 cells cultured on the PHOQ scaffold growing best. After the fifth day, the MC3T3-E1 cells cultured on the PH, PHQ, and PHO scaffolds tended to be consistent, while the cell proliferation rate of the PHOQ scaffold group was significantly increased (p<0.05) compared with the PH, PHQ, and PHO scaffolds, and the reason should be that the internal OGP and the surface QK produced a synergistic effect in the release process. Figure 4 The results show that the PHOQ scaffold has good cell compatibility and promotes cell proliferation, and the reason may be that the internal OGP and the surface QK produced a synergistic effect in the release process.
[0071] (2) Live / dead staining The live / dead assay kit (Beyotime, China) containing Calcein-AM and propidium iodide (PI) was used to evaluate the cytotoxicity of the 3D printed scaffolds. 2x10 4 / each of the MC3T3-E1 cells were seeded on the above-mentioned composite 3D printed scaffolds and incubated for 1 day. After PBS washing, the cells were stained with Calcein / PI solution, and then observed by confocal laser scanning microscope (CLSM, Nikon, Japan) for cell live / dead. The results of the effect of different 3D printed scaffolds on MC-3T3-E1 cell live / dead are shown in Figure 5 Figure 2A, and Figure 2B. In the figures, * indicates p<0.05, ** indicates p<0.01, **** indicates p<0.0001, and the same below. Figure 5 Figure 2A is Calcein / PI staining of different 3D printed scaffolds, and Figure 2B is a bar chart of the live / dead ratio of different 3D printed scaffolds, with a scale of 200 pm.
[0072] Figure 5 Live / dead staining showed that MC3T3-E1 cells had strong adhesion on all four 3D printed scaffolds, PHOQ, PH, PHQ, PHO. There was no significant difference in cell density between the PH scaffold group, the PHO scaffold group, and the PHQ scaffold group (Fig. 4A, B). However, compared with the PH scaffold group, the PHO scaffold group, and the PHQ scaffold group, we observed that the PHOQ scaffold group had higher cell density, the best cell compatibility, and the least number of dead cells, which indicated that the 3D printed scaffold of the PHOQ scaffold group, which combined OGP and QK polypeptides, further enhanced the biological performance of the scaffold, promoted cell survival and adhesion. Figure 5
[0073] (3) Cell morphology 2 x 10 4 cells of MC3T3-E1 were inoculated on the above different composite 3D printed scaffolds, and the cell morphology was observed after 2 days of culture. After 3 times of PBS washing, 4% paraformaldehyde solution was used for fixation for 15 minutes, 0.1% Triton X-100 (Sigma-Aldrich, Burlington, MA, USA) was soaked for 10 minutes, and PBS was washed for 2 times. Phalloidin (phalloidin) and 4, 6-diamino-2-phenylindole dihydrochloride (DAPI, Sigma, MA, USA) were stained overnight and 2 min, respectively, to label actin and nuclei. Then the cell morphology on the scaffold was observed by confocal laser scanning microscope (CLSM, Nikon, Japan). The results of cytoskeleton staining of MC-3T3-E1 cells on different composite 3D printed scaffolds are shown in Fig. 4C, D, and the scale bar is 200 pm. Figure 6
[0074] Figure 6 Fluorescent staining of cytoskeleton showed that the adhesion and spreading of MC3T3-E1 cells on the PHQ and PHOQ group scaffolds were good, and the distribution of PHQ and PHOQ group cells was denser and more extensive than that of PH and PHO group.
[0075] The above experimental results show that the PHOQ scaffold surface coated with a composite hydrogel coating of OGP and QK has better biocompatibility.
[0076] Example 4 Evaluation of in vitro migration and angiogenic performance of different composite 3D printed scaffolds and in vitro osteogenic performance (1) In vitro migration and angiogenic performance of different composite 3D printed scaffolds The in vitro angiogenic effect of the scaffold extract was evaluated by scratch test and tube formation test using human umbilical vein endothelial cells (HUVECs) as experimental objects, as follows: HUVECs were seeded at 5.0 x 105 HUVECs were seeded at a density of 1000 g / well in 12-well plates. After reaching 90% confluence, the cells were starved for 24 hours. Scratches were then created using the tip of a 200 μL pipette, followed by rinsing to remove unattached cells and cell debris. The culture medium was then replaced with an extract of the 3D-printed scaffold (the 3D-printed scaffold extract was prepared according to ISO 10993-12:2021). HUVEC migration was observed under a light microscope at 0, 12, and 24 hours, and the acquired images were analyzed using ImageJ 1.8.0 software. The migration rate was calculated using the formula: Migration Rate (%) = (S0 - S...) / (S0 - S0 ... t ) / S0×100%; where S0 is the initial area of the scratch, S t This represents the area at each time point. Results of the in vitro cell migration performance of different composite 3D-printed scaffolds are as follows: Figure 7 As shown; Figure 7 In Figure A, HUVECs migration experiments outside the scaffolds of different composite 3D printed scaffolds are shown. In Figure B, HUVECs migration rate statistics are shown in the bar chart. * indicates p < 0.05, ** indicates p < 0.01, and *** indicates p < 0.001.
[0077] Tube formation experiments were performed using Matrigel (Sigma, USA). 200 μL Matrigel was added to each well of a 24-well plate and incubated at 37°C for gelation. The extract from the 3D-printed scaffold was then used as the culture medium at a concentration of 2.0 × 10⁻⁶. 4 HUVECs were seeded into each well at a density of 100 cells / well. After 6 hours of culture, they were observed and photographed under a light microscope. For quantitative analysis of the tubular structures, the Angiogenesis Analyzer included with ImageJ 1.8.0 software was used to analyze the length, number of branches, connections, and nodes of the tubular structures. The in vitro tubular formation effect results of different composite 3D printed scaffolds are shown below. Figure 8 As shown in A to C; Figure 8 In the diagram, A represents the tube formation test of HUVECs, B is a bar chart of the number of nodules, and C is a bar chart of the total tube length.
[0078] The expression levels of angiogenesis-related mRNAs were detected by quantitative polymerase chain reaction (qPCR). In brief, total RNA was extracted from human umbilical vein endothelial cells (HUVECs) and reverse transcribed, followed by qPCR analysis using a real-time quantitative thermal cycler (LC96, Roche, Switzerland). The primer sequences used in this embodiment are detailed in Table 1.
[0079] Table 1 Primer sequences for angiogenesis genes Through 2 -△△CtThe relative expression of angiogenesis-related genes was calculated, and β-actin was used as an internal reference gene for normalization. The mRNA expression results of VEGF (vascular endothelial growth factor) and NOTCH1 genes are shown in Figure 8 D and E in the formula, Figure 8 D is the mRNA expression of the VEGF gene, and E is the mRNA expression of the NOTCH1 gene.
[0080] In order to determine the angiogenesis induction performance of different 3D printed scaffolds, angiogenesis test and HUVEC migration test were used. Figure 7 The HUVEC migration experiment showed that compared with the PH group scaffold, the PHO group, PHQ and PHOQ group scaffolds could significantly improve the migration ability of HUVEC after co-culturing for 12h, and the migration rate of the PHOQ group was the highest among the four groups, and the cell migration speed was significantly greater than that of the PH group. However, after incubation for 24h, there was no statistical difference between the PHO group and the PHQ group, but compared with the PHO group and the PHQ group, the PHOQ group scaffold could further enhance the migration of HUVEC (p<0.05), indicating that OGP and QK on the PHOQ group scaffold could synergistically promote and accelerate the migration of HUVEC.
[0081] And Figure 8 The tube formation experiment results showed that whether in the total length of the formed tube or in the number of nodes, the PHOQ group was significantly better than the PH group, the PHO group and the PHQ group. Among them, the mRNA expression of VEGF and NOTCH1 genes of the PHQ scaffold group and the PHOQ scaffold group was significantly higher than that of the PH scaffold group and the PHO scaffold group, and the high expression of VEGF and Notch1 could promote angiogenesis, which confirmed that QK was gradually released from the scaffold surface, significantly enhancing the angiogenesis induction ability of the scaffold. These findings showed that the PHOQ scaffold had enhanced angiogenesis characteristics after QK hydrogel coating on the surface. This composite material retained the biological activity of QK and met the requirements of angiogenesis induction in bone regeneration, solving the challenge of insufficient new blood vessel formation in bone healing.
[0082] (2) Evaluation of the in vitro osteogenic performance of different composite 3D printed scaffolds MC3T3-E1 cells were seeded at a density of 5.0×10 5Cells were seeded at a density of [number] cells / well in 12-well plates. The culture medium was Dulbecco's modified Eagle's medium (DMEM, Gibco) supplemented with 10% fetal bovine serum (FBS, Gibco), mixed 1:1 with the scaffold extract, and the medium was changed every other day. After 14 days of culture, cells in each group were fixed with 4% paraformaldehyde solution and then stained with alkaline phosphatase (ALP) (Beyotime, China). The stained cells were observed under a light microscope and analyzed using ImageJ 1.8.0 software. After 21 days of culture, the degree of extracellular matrix mineralization was determined using Alizarin Red S (ARS, Beyotime, China) staining, and the resulting images were analyzed using ImageJ 1.8.0 software. The in vitro osteogenic induction performance evaluation results of different composite 3D-printed scaffolds are shown below. Figure 9 As shown, Figure 9 In the chart, A represents alkaline phosphatase (ALP) staining, B represents alizarin red (ARS) staining, C represents a bar chart showing the percentage of ALP-positive areas, and D represents a bar chart showing the percentage of ARS-positive areas.
[0083] like Figure 9 As shown in Figure A, a small amount of ALP staining (blue-purple) areas were observed in the PH and PHQ groups, while significantly more ALP-positive areas were found in the PHO and PHOQ groups, with the deepest staining depth in the PHOQ group. ALP activity assays also showed that the PHOQ group exhibited the most significant expression among all groups (mean positive staining area percentage was 55.16±4.48%), followed by the PHO group, with a staining area of 47.24±3.65%. Figure 9 (C). These findings suggest that the presence of HA within the scaffold combined with sustained OGP release can improve osteogenic differentiation of MC3T3-E1 cells.
[0084] Figure 9 The B-mode image shows the calcium deposition effect in MC3T3-E1 cells cultured in different scaffold extracts for 21 days. ARS staining showed a similar trend to ALP staining. The PHO and PHOQ groups induced more calcium nodule formation than the PH and PHQ groups. The PHOQ group showed the highest mineralization level (mean positive area 30.90±2.49%), and the positive area in the PHOQ group was significantly increased compared to the PH, PHO, and PHQ groups (p<0.05). Figure 9 (D). The superior osteogenic induction capacity exhibited by the PHOQ group can be attributed to the synergistic effect of the dual release of QK and OGP within the scaffold on the mineralization of MC3T3-E1 cells.
[0085] The above experimental results show that the PHOQ scaffold has excellent abilities to promote angiogenesis and osteogenic induction, can release QK to promote angiogenesis in time sequence, and then continuously release OGP to synergistically promote bone regeneration. This is consistent with the physiological self-healing process of bone injury, and the PHOQ scaffold can be used as a bone repair biomaterial to promote bone defect repair.
[0086] Example 5 in vivo verification of animal experiments Diabetes inhibits osteoblast differentiation and proliferation and promotes osteoclast activity, resulting in reduced bone formation, decreased bone density, and decreased bone regeneration ability through high blood sugar, accumulation of advanced glycation end products (AGEs), increased reactive oxygen species (ROS), and inflammation. To verify that the PHOQ scaffold can be used as a medical material for bone repair to promote bone defect repair, this embodiment first constructs a diabetic animal model and then artificially causes bone injury to simulate the application scenario with low self-bone regeneration healing ability.
[0087] 1. Modeling and grouping (1) Animal feeding: 300 g male (Sprague-Dawley, SD) rats were purchased from the Guangdong Experimental Animal Center and raised in Shenzhen Lingfu Top Biological Technology Co., Ltd., with free water and 12-hour light alternation. The animal experiment plan was approved by the Shenzhen Lingfu Top Biological Technology Co., Ltd. Animal Ethics Committee (Project Number: IACUC NO: 2023-0302).
[0088] (2) Establishment of diabetic animal model: After an adaptation period of 7 days, the rats were placed in a state of fasting for 24 hours, then intraperitoneally injected with 75 mg / kg of streptozotocin (STZ). Three days later, blood glucose was detected, and if the blood glucose level was higher than 16.1 mmol / L, the diabetic rat model was considered to be successfully established.
[0089] (3) Anesthesia and surgical preparation: SD rats were anesthetized with isoflurane gas and maintained anesthesia with a breathing mask. After anesthesia, the rat's head was prepared for skin, and the head hair was removed with a razor. The limbs were fixed in a prone position. After iodophor disinfection, a 1.5 cm long incision was made along the midline of the head, and then a dental drill was used to drill a circular critical size bone defect with a diameter of 5 μm.
[0090] (4) Experimental intervention and postoperative treatment: The SD rat skull defect area was filled with different composite 3D printed scaffolds, respectively marked as PH, PHO, PHQ and PHOQ groups, and the incision was closed layer by layer. After the operation was completed, the rats were raised in separate cages, and all experimental rats were given 30 mg / kg of ampicillin and 2 mg / kg of meloxicam to prevent infection and relieve pain.
[0091] 2. Micro-CT scanning At 4 and 8 weeks postoperatively, the rats were sacrificed by intraperitoneal injection of an overdose of water-soluble chloral hydrate and the skull tissues were removed. The skull regeneration and bone density were scanned and reconstructed using a Micro-CT (NEMO, China) with a detection parameter of 80 kV voltage, 100 μA current, and 18 μm voxel size. The collected skull cross-section slices were reconstructed into three-dimensional images using the accompanying reconstruction software with a gray scale setting of 220. The three-dimensional bone morphometry was used to determine the skull regeneration new bone volume, bone volume / total volume (BV / TV), and bone mineral density (BMD) of the diabetic rats. The micro-CT scanning analysis results of the different composite 3D printed scaffolds for repairing skull defects in diabetic rats are shown in Figure 10 Figure 10 A is Micro-CT scanning reconstruction, B is bone mineral density (BMD), C is BV / TV, and D is regenerated bone volume.
[0092] 3. Animal sampling and embedding sectioning (1) Decalcification: After Micro-CT scanning, the skull tissues were fixed in 4% paraformaldehyde at room temperature for 24 h, washed with tap water to remove residual formaldehyde, and then immersed in 20% EDTA decalcification solution for decalcification, with liquid exchange twice a week.
[0093] (2) Tissue trimming: After decalcification, the skull samples were again washed with running water, trimmed of excess tissue, and cut along the midline. The samples were then placed in embedding boxes and washed with running water for 4 h to remove residual fixative.
[0094] (3) Dehydration and transparency: The samples were placed in 50%, 75%, 85%, 95%, 100%, and 100% alcohol solutions for 2 h each for dehydration. The dehydrated samples were then placed in xylene for 2 times of transparency treatment, each for 30 min.
[0095] (4) Wax immersion and embedding: The transparent treated skull samples were then placed in melted paraffin solution for 3 times of wax immersion, each for 2 h. After sufficient wax immersion, the skull samples were placed in an embedding machine for embedding.
[0096] (5) Sectioning: The embedded skull samples were fixed on a microtome for sectioning, with a section thickness of 4 μm. After sectioning, the sections were placed in a 65°C oven for 6 h for baking and were ready for use.
[0097] To further evaluate the quality of rat skull bone regeneration, HE and Masson staining were used for histological analysis, as follows: 4. HE staining (1) Dewaxing and rehydration: The above-mentioned skull tissue sections were baked at 65°C for 30 minutes and then dewaxed and rehydrated. They were immersed in xylene twice for dewaxing, each time for 15 minutes. Then, they were rehydrated by passing through 100%, 95%, 85%, 75% and 50% alcohol solutions in stages, each gradient treatment for 2 minutes. Finally, they were placed in tap water for the next step of processing.
[0098] (2) Hematoxylin staining: Immerse the sections in hematoxylin dye for 5 minutes and wash thoroughly with water.
[0099] (3) Color separation: Immerse the slices in 1% (v / v) hydrochloric acid alcohol solution for 5-7 seconds, then quickly remove and wash with water.
[0100] (4) Blue inversion: Immerse the slices in ammonia water (1:400) for 1 minute to invert blue, then remove and wash with water again.
[0101] (5) Eosin staining: Immerse the section in 75% ethanol solution for 30 seconds, remove and spin dry, then immerse in eosin dye for 40 seconds, and quickly remove and wash with water.
[0102] (6) Mounting: Immerse the slides in 100% ethanol for 1 minute, remove and air dry, then mount with neutral quick-drying gel. HE staining results are as follows. Figure 11 As shown in A, Figure 11 The "▲" in the middle represents a 3D-printed scaffold, the same below; NB represents newly formed bone, LB represents lamellar bone; TB represents total regenerated bone. Figure 11 In the middle, C is a bar chart of NB / TB statistics, and D is a bar chart of LB / TB statistics.
[0103] 5. Masson staining (1) Dewaxing and rehydration: Same as above.
[0104] (2) Iron hematoxylin staining: outline the tissue area with an immunohistochemical pen, add iron hematoxylin dye and stain for 5 minutes, then wash thoroughly with water.
[0105] (3) Color separation: Same as above.
[0106] (4) Spring Red Staining: Add Spring Red dye and stain for 2 hours, then wash thoroughly with water.
[0107] (5) Phosphomolybdic acid color separation: Add 1% phosphomolybdic acid solution for color separation treatment for 1 minute.
[0108] (6) Aniline blue staining: Add aniline blue dye for 2 minutes and then spin dry.
[0109] (7) Wash with glacial acetic acid: Immerse the slices in 1% glacial acetic acid solution for 10 seconds.
[0110] (8) Mounting: Same as above. Masson staining results are as follows. Figure 11 As shown in B.
[0111] 6. Immunohistochemistry (1) Dewaxing and rehydration: same as above.
[0112] (2) Antigen retrieval: the sections were immersed in antigen retrieval solution and heated by microwave for 8 min, then added with pure water to make up the evaporated volume, heated again for 8 min, and then recovered to room temperature before being washed with water. The types of antigen retrieval solution are shown in Table 4.
[0113] (3) Blocking and inactivation: the sections were immersed in peroxidase blocking solution for 15 min, and then washed with water.
[0114] (4) Blocking: the tissue area was outlined with an immunohistochemical pen, and goat serum was added and incubated for 40 min.
[0115] (5) Primary antibody incubation: the sections were dried, and the primary antibody was added to cover the tissue, and then incubated in a wet box at 4°C overnight. The next day, the sections were recovered to room temperature, and then washed with water. The dilution ratio of the primary antibody was ALP (1:500 dilution, ET1601-21, HUABIO) and OCN (1:250 dilution, ER1919-20, HUABIO).
[0116] (6) Secondary antibody incubation: the secondary antibody (1:250 dilution) was added and incubated at room temperature for 40 min, and then washed with water.
[0117] (7) Color development: 1 mL of diamino benzidine (DAB) diluent was added with 1 drop of DAB concentrate to prepare a working solution. The DAB working solution was added to cover the tissue. The color development was terminated under a microscope when obvious brown color appeared and was clearly distinguished from the surrounding tissue, and then washed with water.
[0118] (8) Hematoxylin staining: the sections were immersed in hematoxylin dye for 1 min, and then washed with water.
[0119] (9) Differentiation: same as above.
[0120] (10) Mounting: same as above. The results of the evaluation of the osteogenic performance of different composite 3D printed scaffolds for repairing skull defects in diabetic rats are shown in Table 5. Figure 12 Figure 12 Table 5: Evaluation of the osteogenic performance of different composite 3D printed scaffolds for repairing skull defects in diabetic rats
[0121] 7. Immunofluorescence (1) Dewaxing, rehydration, antigen retrieval, peroxidase inactivation, and blocking: same as above.
[0122] (2) Primary antibody incubation: spin dry the sections, add primary antibody, cover the tissue completely, and incubate in a wet box at 4°C overnight. The next day, after rewarming, wash thoroughly. The dilution ratio of the primary antibody is CD206 (1:1000 dilution, ab300621, Abeam), CD31 (1:1000 dilution, ab281583, Abeam).
[0123] (3) Secondary antibody incubation: add Alexa Fluor 594 and Alexa Fluor 488 fluorescent secondary antibodies (1:250 dilution) respectively, incubate at room temperature for 40 minutes, and then wash thoroughly.
[0124] (4) Add DAPI-containing glycerol mounting medium for sealing, and observe under a laser microscope. The results are shown in Figure 13 . The results of the evaluation of the immunization and angiogenesis performance of different composite 3D printed scaffolds for repairing skull defects in diabetic rats are shown in Figure 13 . Figure 13 A is CD206 immunofluorescence staining, B is CD31 staining, C is a CD206 statistical column chart, D is a CD31 statistical column chart, and E is a blood vessel diameter statistical column chart. "▲" represents a 3D printed scaffold.
[0125] Animal experiment results: (1) Micro-CT scanning As shown in Figure 10 , after 4 and 8 weeks of scaffold implantation, bone regeneration was only found in the peripheral part of the rat skull defect in the PH and PHQ groups, and cavities could still be seen between the scaffold struts, indicating insufficient new bone formation. Although the cavities in the PHO scaffold were filled with new bone tissue after 8 weeks, there was still a gap between the scaffold and the defect boundary. In contrast, the PHOQ scaffold greatly improved the bone regeneration of the skull defect, with the gap between the defect boundary and the scaffold cavity being filled with newly regenerated bone tissue. As can be seen from Figure 10 A, after 4 and 8 weeks of implantation, Micro-CT scanning results showed that the PHOQ group dominated in all measured parameters of bone regeneration. The BV / TV ratio was calculated as 7.87±0.61% and 15.93±0.55% respectively (p<0.05, vs PH, PHO and PHQ groups) (B in Figure 10 ). The bone volume / total volume (BV / TV) and bone mineral density (BMD) were significantly increased (p<0.05 compared with the PH, PHO and PHQ groups). The bone mineral density (BMD) was significantly increased, and the BMD of the PHOQ group was 1.15±0.01 g / cm 3 and 1.24±0.01 g / cm 3 after 4 and 8 weeks of implantation respectively (p<0.05 compared with the PH, PHO and PHQ groups) (B in Figure 10(C). Furthermore, compared to the PH and PHQ groups, although the PHO group also showed significantly enhanced bone regeneration indices, with marked increases in new bone mass, BV / TV, and BMD (p<0.05), the new bone mass in the PHOQ group was only 3.93±0.33 mm. 3 and 7.13±0.22mm 3 The value was significantly higher than the other three groups (p<0.05). Figure 10 (Middle D). The enhanced osteogenic activity observed in these results, particularly in scaffolds containing OGP (PHO and PHOQ groups), confirms that OGP is an effective active ingredient for stimulating bone regeneration. The PHOQ scaffold induced the highest levels of bone regeneration volume and density, which can be attributed to the synergistic effect of angiogenesis and osteogenic activity induced by QK and OGP release.
[0126] (2) HE and Masson staining Depend on Figure 11 HE staining results showed that, 4 weeks after scaffold implantation, significant new cell migration could be observed near the scaffolds in the PHO, PHQ, and PHOQ groups, with deeper staining and more pronounced cell infiltration observed in the PHOQ group. Figure 11 (A). Furthermore, new bone formation was observed above the scaffold in the PHOQ group at 4 and 8 weeks after implantation, and new bone formation also appeared around the scaffold in the PHO group at 8 weeks.
[0127] Depend on Figure 11 Masson staining results showed that at 4 and 8 weeks after scaffold implantation, only limited new bone tissue and blood vessels were observed around the PH group scaffold; while the PHQ group showed significantly more blood vessels, but new bone formation was still insufficient, and cell migration around the scaffold was inadequate. This indicates that the release of pro-angiogenic biomolecules can effectively improve vascularization, but in the process of tissue regeneration, the presence of pro-angiogenic biomolecules alone in the scaffold cannot effectively enhance bone regeneration. In contrast, the PHO group scaffold showed significantly more new bone formation and cell infiltration, and at 8 weeks, red calcified lamellar bone structures appeared on the scaffold surface, including some blood vessels. The PHOQ group scaffold not only induced new bone formation but also showed significant cell infiltration, and the diameter of the newly formed blood vessels around it was also larger. Figure 11 (B) It is worth noting that the upper layer of the scaffold in the PHOQ group showed a significantly thicker calcified lamellar bone structure, a feature that was more prominent than that in the PHO group.
[0128] Further analysis was conducted to quantify the evaluation of regenerated bone by analyzing the ratio of newly formed bone area to total bone area (NB / TB) and the ratio of lamellar bone area to total bone area (LB / TB). The results were consistent with the observed phenomena; both the PHO and PHOQ groups showed higher NB / TB and LB / TB ratios at 4 and 8 weeks, indicating greater collagen fiber deposition in the bone defect area. Figure 11 (C and D) Among them, the PHOQ group showed better bone regeneration. Eight weeks after implantation, the NB / TB and LB / TB ratios of all groups increased significantly. The NB / TB ratio of the PHOQ group was 48.57±0.89%, and the LB / TB ratio was 25.54±0.79%, both significantly higher than those of the PH and PHQ groups. These experimental results confirm the beneficial effects of integrating OGP osteogenic growth peptides into 3D-printed scaffolds. Furthermore, coating the OGP-loaded scaffold with the angiogenic factor QK further endows it with excellent angiogenic capacity and effectively induces the regeneration of large-diameter vessels, thereby compensating for the insufficient bone regeneration of QK alone and further enhancing the ability of OGP to promote new bone formation and calcification in patients with bone defects. This also indicates that the PHOQ scaffold is a composite bone tissue engineering scaffold with dual QK and OGP delivery functions, serving as an ideal platform for enhancing bone tissue regeneration and achieving the desired vascularization, and can be used to prepare bone repair biomaterials to promote the regeneration and repair of defective or damaged bone tissue.
[0129] (3) Immunohistochemistry Depend on Figure 12 Results A and B show that 4 weeks after stent implantation, ALP staining revealed significantly higher ALP expression levels in the PHO and PHOQ groups compared to the PH and PHQ groups (p<0.05). Specifically, the ALP expression area ratio in the PHO group was 4.75±0.59%, while it was 5.67±0.43% in the PHOQ group. Notably, 8 weeks after implantation, the ALP area ratio in the PHO group increased to 5.67±0.54%, while it increased to 7.08±0.70% in the PHOQ group. Compared to the PHO group, the PHOQ group showed significantly higher ALP levels (5.67±0.54% vs 7.08±0.70%, p<0.05), and also significantly higher than the PHQ group (p<0.001), indicating a significant increase in ALP osteogenic expression over time after PHOQ stent implantation.
[0130] Figure 12 The staining results of OCN in the middle are consistent with the trend observed in ALP staining results. Figure 12(C and D). Notably, at 4 and 8 weeks post-implantation, the OCN expression levels in the PHO and PHOQ groups were significantly higher than those in the PH and PHQ groups (p<0.05). Specifically, the OCN expression level in the PHO group was 5.92±0.23% at 4 weeks and 7.04±0.09% at 8 weeks; while the OCN expression level in the PHOQ group was 6.84±0.44% at 4 weeks and 8.07±0.34% at 8 weeks (p<0.05). Figure 12 (C, D) This indicates that OCN, as a late-stage osteogenic marker, showed significantly higher expression levels than ALP at 8 weeks, and the OCN-positive rate in the PHOQ group was significantly higher than that in the PHO group at 8 weeks (p<0.05). Furthermore, at 8 weeks, the expression levels in the PHOQ group were significantly higher than the other three groups in both ALP and OCN staining (p<0.05). These results demonstrate that the PHOQ scaffold possesses optimal osteogenic capacity, promoting osteoogenesis not only in the early stages but also enhancing bone mineralization in the later stages. This proves that the time-released QK and OGP in this 3D-printed scaffold (PHOQ scaffold) synergistically promote better bone formation.
[0131] The host's innate immune response also plays a crucial role in bone regeneration. CD206 (also known as the mannose receptor) is a transmembrane glycoprotein involved in tissue repair, anti-inflammatory responses, and immune regulation. It is a marker of M2 macrophages and is closely related to their anti-inflammatory and tissue repair functions. In this embodiment, the immunofluorescence of CD206 was also used to evaluate the immunomodulatory effects of the 3D-printed scaffold in vivo. Figure 13 The results from the study showed that, 14 days after stent implantation, CD206 expression gradually increased across the PH, PHO, PHQ, and PHOQ groups. The CD206 expression level in the PHQ group was 1.37±0.14%, significantly higher than that in the PH and PHO groups (p<0.05). The PHOQ group showed the strongest expression, at 1.98±0.15% (significantly higher than the PH, PHO, and PHQ groups, p<0.05). Figure 13 (C). In this experiment, the enhanced expression of these CD206 cells may be related to the combined anti-inflammatory effects of QK and OGP. QK has been reported to indirectly induce M2 macrophage polarization by regulating the VEGF signaling pathway. OGP has also been shown to have osteogenic and immunomodulatory effects, possibly by promoting the secretion of anti-inflammatory factors and increasing the positive proportion of M2 macrophages, thereby reducing local inflammatory response and improving the bone repair environment.
[0132] To further elucidate the angiogenesis potential of 3D-printed scaffolds in vivo, we conducted a detailed study on their implantation efficacy. Fourteen days after implantation, the expression of CD31, a typical vascular biomarker around the scaffold, showed an increasing trend across groups. Figure 13Statistical analysis of CD31 positive area showed that the positive area of PHQ group was 4.39±0.49%, which was significantly larger than that of PH group and PHO group (p<0.05). The positive area of PHOQ group was 5.81±0.59%, which was significantly larger than that of the other three groups (p<0.05). Notably, the diameter of the new blood vessels around the stent of PHOQ group was significantly increased compared with PH and PHO groups, which was 17.65±2.17 μm (p<0.05). In contrast, the diameters of the blood vessels of PH, PHO and PHQ groups were all less than 15 μm, which indicated that QK and OGP of PHOQ stent could also effectively synergistically promote the generation of new blood vessels in vivo Figure 13 Fig. 12 shows the results of the statistical analysis of the CD31 positive area in the middle B). Statistical analysis of the CD31 positive area showed that the positive area of PHQ group was 4.39±0.49%, which was significantly larger than that of PH group and PHO group (p<0.05). The positive area of PHOQ group was 5.81±0.59%, which was significantly larger than that of the other three groups (p<0.05). Notably, the diameter of the new blood vessels around the stent of PHOQ group was significantly increased compared with PH and PHO groups, which was 17.65±2.17 μm (p<0.05). In contrast, the diameters of the blood vessels of PH, PHO and PHQ groups were all less than 15 μm, which indicated that QK and OGP of PHOQ stent could also effectively synergistically promote the generation of new blood vessels in vivo
[0133] Those skilled in the art will readily understand that the above described are only the preferred embodiments of the present application, and are not intended to limit the present application. Any modification, equivalent replacement and improvement made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for the preparation of a composite 3D printed scaffold with temporal regulation of vascularization and bone tissue regeneration, characterized by, Comprising the following steps: loading osteogenic inducer and vascular induction differentiation agent into two carrier materials with different degradation rates respectively, and printing in reverse order of physiological repair process of vascularization first and then osteogenesis; mixing slow-release carrier loaded with osteogenic inducer and nano-hydroxyapatite, and then 3D printing at low temperature below 0℃ to make scaffold bone framework, which is loaded with slow-release osteogenic inducer at the same time; then coating fast-release carrier loaded with vascular induction differentiation agent on the 3D printed scaffold framework to construct composite 3D printed scaffold with different layers, so that the inner layer is loaded with osteogenic inducer and the outer layer is loaded with vascular induction differentiation agent; the osteogenic inducer comprises BMP-2 and OGP peptide; and the vascular induction differentiation agent comprises VEGF and QK peptide.
2. The production method according to claim 1, wherein the osteogenic inducer is OGP peptide, and its amino acid sequence is shown in SEQ ID NO: 1, SEQ ID NO: 2, SEQ ID NO: 3, or SEQ ID NO:
4.
3. The production method according to claim 2, wherein the vascular induction differentiation agent is QK peptide, and its amino acid sequence is shown in SEQ ID NO: 5, SEQ ID NO: 6, SEQ ID NO: 7, SEQ ID NO: 8, or SEQ ID NO:
9.
4. The production method according to any one of claims 1 to 3, characterized by, the low temperature is 0℃ to -20℃.
5. The production method according to claim 4, wherein mixing at a mass ratio of slow-release carrier, nano-hydroxyapatite and OGP peptide of 200:100:1 to 160:40:1, and co-melting in 1,4 dioxane solution; low-temperature printing using a 3D printer, and the printing parameters are as follows: printing speed of 20-55 mm / s, pneumatic pressure of 80-150 kPa, receiving plate temperature of -10℃ to -20℃, and printing needle of 27G; after 3D printing, the scaffold framework is freeze-dried at low temperature; the slow-release carrier is a hydrophobic polymer; then immersing the freeze-dried scaffold framework in a fast-release carrier solution containing QK peptide, and using ultraviolet light for photocuring to obtain a composite 3D printed scaffold with time-regulated vascular and bone tissue regeneration; the fast-release carrier is a hydrogel material or a hydrophilic polymer.
6. The production method according to claim 5, wherein the slow-release carrier is selected from PLGA and PCL; and the fast-release carrier is selected from gelatin, sodium alginate, collagen and methacrylated dextran.
7. The production method according to claim 6, wherein the fast-release carrier is methacrylated dextran, and the mass ratio of QK peptide to methacrylated dextran is 1:50 to 1:
100.
8. A composite 3D printed scaffold with temporal regulation of vascularization and bone tissue regeneration, characterized in that, obtained by the preparation method according to any one of claims 1 to 7.
9. Application of a composite 3D printed scaffold with time-regulated vascular and bone tissue regeneration in preparing a bone defect self-repairing medical material.
10. Use according to claim 9, wherein the composite 3D printed scaffold is applied to prepare a diabetic bone defect self-repairing medical material.
Citation Information
Patent Citations
Submicron nucleocapsid microsphere material capable of releasing active factors on time and preparation method of submicron nucleocapsid microsphere material
CN104096263A
3D print scaffold material and preparation method and application thereof
CN107115561A
Preparation method of traditional Chinese medicine monomer sequence slow-released calcium-phosphorus support material for osteogenesis and angiogenesis
CN108434518A
Composite scaffold as well as preparation method and application thereof
CN116370704A
Preparation method and application of 3D printed porous composite scaffold
CN119838058A
Cited By
A biodegradable magnesium alloy cardiovascular stent surface double-layer functional coating and its preparation method
CN122399122A
